1982
DOI: 10.1088/0031-9155/27/10/001
|View full text |Cite
|
Sign up to set email alerts
|

Optimum X-ray spectra for mammography

Abstract: A number of authors have calculated x-ray energies for mammography using, as a criterion, the maximum signal-to-noise ratio (SNR) obtainable per unit dose to the breast or conversely the minimum exposure for constant SNR. The predicted optimum energy increases with increasing breast thickness. Tungsten anode x-ray spectra have been measured with and without various added filter materials to determine how close the resultant spectra can be brought to the predicted optimum energies without reducing the x-ray out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
(7 reference statements)
2
22
0
1
Order By: Relevance
“…beam quality, an optimum working voltage of 28 kVp with the Mo/Mo target-filter combination has been selected for all of the tests. This conclusion was also confirmed by other studies in the literature (17)(18)(19). The optimal combinations of 30 F-S pairs were investigated in this work by sensitometry and total performance phantom and efficiency measurements.…”
Section: Discussionsupporting
confidence: 87%
“…beam quality, an optimum working voltage of 28 kVp with the Mo/Mo target-filter combination has been selected for all of the tests. This conclusion was also confirmed by other studies in the literature (17)(18)(19). The optimal combinations of 30 F-S pairs were investigated in this work by sensitometry and total performance phantom and efficiency measurements.…”
Section: Discussionsupporting
confidence: 87%
“…In mammography the possibility of adapting radiation quality to object thickness by selection of the tube voltage alone is very limited together with the conventional molybdenum anode-molybdenum filter system (Gajewski and Reiss 1974;Jennings et al 1981;Beaman et al 1982;Aichinger et al 1994;S€ abel and Aichinger 1996). The relative energy distribution of the X-ray photons (i.e.…”
Section: Mammographymentioning
confidence: 99%
“…Recently, it has been suggested that x-ray tubes with tungsten anodes used with palladium filters would give images comparable to molybdenum tubes (7,8,30). An example of a primary mammographic spectrum at 30 kYp with a tungsten anode is also shown in Fig.…”
Section: Basic Considerationsmentioning
confidence: 99%